(untitled) (Colombia Medica, 1984)
The practice of psychiatry in Colombia was traditionally reduced to two very different systems: endless hours of psychotherapy in private practice or prolonged interment in insane asylums. A mental health program involves services for prevention and treatment of mental disorders, the rehabilitation of former psychiatric patients and the promotion of mental health. Several drastic changes have taken place in psychiatry in this country in the last twenty years. They look for more efficient ways to treat mental illness and at the same time, to reduce the number of people needing psychiatric help. To alter the traditional way of diagnosis and treatment of the mentally ill is a tangible contribution of psychiatry in Colombia not only to the care of mental disorder bur to the promotion of the individual and community welfare.